Evaluación de la calidad de fiscalización en obras de edificaciones públicas en la provincia de Chimborazo. - Escudero Moyón, Jennifer Cristina (2026)
This research evaluates the quality of oversight in public building projects in Chimborazo, analyzing the management of supervisors in 17 buildings constructed between 2020 and 2024, considering: the degree of compliance with the parameters of scope, cost, and time; and the quantitative and qualitative evaluation of the inspector's management through surveys of the contractor, inspector, and beneficiary of each project. By comparing quantitative and qualitative data, the quality of oversight was evaluated based on compliance with criteria established in accordance with current Ecuadorian regulations. The quality of oversight was categorized into four levels, from Level 1 (very low relative quality) to Level 4 (highest relative quality). Most of the oversight processes evaluated (52.94%) were of very low relative quality and low quality, while only 17.65% were of higher relative quality. These results show that most of the oversight of public buildings in Chimborazo does not meet the quality objective, which highlights the need to implement measures to improve the quality of oversight processes. This research also shows fundamental data such as compliance with parameters in evaluated works, main errors or omissions in the functions of supervisors, the influence of supervision quality on the quality of works, and construction deficiencies in works, which generate risks in fulfilling the purpose for which they were built.